AN UPDATED SYNOPSIS OF LUDWIGIA (ONAGRACEAE) IN MALESIA - Ian Turner (BRIN Publishing (Penerbit BRIN), 2021)
TURNER, I. M. 2021. An updated synopsis of Ludwigia (Onagraceae) in Malesia. Reinwardtia 20(1): 9–16. — A synopsis of the seven native or naturalised species of Ludwigia (Onagraceae) occurring in Malesia is presented. The newly established Ludwigia leptocarpa is included. The paper incorporates a key to the species, synonymy and typification. Lectotypes are designated for 25 names, including five at the second step.